Juridical Analysis of Delegation of Authority Medical Treatment (Verdict Case Study NO.1165/PID.B/2010/PN.SDA, NO.1166/PID.B/2010/PN.SDA, NO.1167/PID.B/ 2010/PN. SDA.) - Juliana Susanti Gunawan; M. Nasser; Petrus Soerjowinoto (SOEPRA, 2018)
Since September 2014, The House of Representatives passed a new Nurses Act, Act Nr.38 of 2014. Nurses Act is considered legal protection for nurses in Indonesia and defines their scope of practice. The Act was developed and passed with the specific aim to improve professional quality and the quality of nursing care. Nurses are legally permitted to prescribe limited medical treatment based on physicians' delegation or mandated orders. All of these actions will be regulated by codes from the Ministry of Health, which will be derived from the new Nurses Act and with consideration of the nurse's competencies to perform such specific medical interventions. This study to examine the extent to which the doctor as general practitioner delegated medical treatment to the nurses and to analyze procedure towards authority delegation from doctor to nurses. As usual, both doctor and nurses were reluctant to have minor clinical treatment delegated and a majority did not think that nurses should carry out delegated diagnostic procedures. Doctors and nurses who had completed their training were more likely to favor delegation since this decade so that delegation may become more common, for example in favor of delegating injections, dressings and stitch removal and immunizations. There is no clear definition of the scope of practice for the nurse in the field, in contrary delegation among those with unfavorable views often appeared formidable. Nurses need reeducating before such a system could. It is dangerous to have someone who'sundertrained.The delegation of medical treatment should consider patient safety and comfort. This research applied the normative juridical method with legal clinical research (prescriptive normative) based on library approach, and case approach consisted of secondary data that gathered by rules, regulations, and verdict case number 1165/Pid.B/2010/PN.SDA, 1166/Pid.B/2010/PN.SDA and 1167/Pid.B/2010/PN.SDA and interviews with a law firm and legal consultant who handled the case verdict about delegation of authority medical treatment from a doctor to nurse. The result of the study showed there are limitation procedures of regulation to perform medical treatments based on physicians' delegation or mandated orders. Therefore health policymaker should make regulations of the scope of medical treatment procedure based on responsibility and authority delegation from doctor to nurse.